Impossibility : the Limits of Science and the Science of Limits. - Barrow, John D. (Oxford University Press, USA, 1999)
In Impossibility, John D. Barrow--one of our most elegant and accomplished science writers--argues convincingly that there are limits to human discovery, that there are things that are ultimately unknowable, undoable, or unreachable. Barrow first examines the limits of the human mind: our brain evolved to meet the demands of our immediate environment, and much that lies outside this small circle may also lie outside our understanding. He investigates practical impossibilities, such as those imposed by complexity, uncomputability, or the finiteness of time, space, and resources. Is the universe.